IMPLEMENTASI PROGRAM KELUARGA HARAPAN SEKTOR PENDIDIKAN DI KELURAHAN MOLAS KECAMATAN BUNAKEN KOTA MANADO - PONTOH, ANASTASYA; POSUMAH, JOHNNY; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2019)
The Hope Family Program is a program approved to develop a system of social protectionfor the poor in Indonesia. One final goal of PKH is to increase school enrollment rates for RTSM childrenspecifically at the elementary, middle and high school levels, and to reduce the number of underageworkers in Indonesia. PKH in this education sector asks RTSM motivation to be able to immediatelyaccept children to school and encourage them to fulfill commitments in the learning process, at least85% of effective days of schooling in one month during the teaching year. The purpose of this study is todescribe the implementation of the Family Hope Program in the education sector in the Molas Sub-District, Bunaken District, Manado City. This research uses descriptive-qualitative method, datacollection techniques carried out by interviews, documentation, and data collection with documents.Randall Ripley and Grace Franklin. This theory looks at the level of approval variable in the applicableregulations, the smooth variable performs the routine and the absence of discussion, the variablerealization of the performance and the desired change. The results of his research showed that theimplementation of PKH in Molas Sub-District, Bunaken District, Manado City was still in theimplementation stage. Dissemination and assistance have not been carried out in full, there have beendelays in disbursing PKH funds and the utilization of PKH funds in the education sector that are not welltargeted. KPM's mindset is wrong regarding children's education.Keywords: Implementation, Hope Family Program Education.